SISTEM EKONOMI PERKEBUNAN: PERSISTENSI KETERGANTUNGAN NEGARA DUNIA KETIGA - Purwandari, Heru (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
There was changing in dependency of the economic plantations system in along time. Two phenomena which always occur is the smallholding estate system are poverty and underdevelopment. In the colonial period, though plantation integrated to the external world, but farmer plantation never change from dependency situation which was created by colonial government. At present, when globalization become ideology that condition has not change. In the makro context, dependency in plantation on colonial period was showed by authority for source of economic. At present, dependency have influence in political government. All of government programs have implication in stagnancy of dependency nature.